A new ZVS full-bridge DC-DC converter for battery charging with reduced losses over full-load range - Kanamarlapudi, Venkata Ravi Kishore (2020)
A new zero-voltage switching full-bridge dc-dc converter for battery charging is proposed in this paper. The proposed isolated dc-dc converter is used for the dc-dc conversion stage of the electric vehicle charger. The primary switches in dc-dc converter turn-on at zero voltage over the battery-charging range with the help of passive auxiliary circuit. The diode clamping circuit on the primary side minimizes the severity of voltage spikes across the secondary rectifier diodes, which are commonly present in conventional full-bridge dc-dc converters. The main switches are controlled with an asymmetrical pulse-width modulation (APWM) technique resulting in higher efficiency. APWM reduces the current stress of the main switches and the circulating losses compared with the conventional phase-shift modulation method by controlling the auxiliary inductor current over the entire operating range of the proposed converter. The steady-state analysis of auxiliary circuit and its design considerations are discussed in detail. A 100-kHz 1.2-kW full-bridge dc-dc converter prototype is developed. The experimental results are presented to validate the analysis and efficiency of the proposed converter.